Strategi Komunikasi Komunitas Olahraga Kalistenik Street Workout Velo dalam Meningkatkan Kesadaran Masyarakat Kelapa Gading akan Pentingnya Olahraga - Mario Komarindo Saputra; Iin Soraya; Cindya Yunita Pratiwi (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
This study discusses the communication strategy of the Street Workout Velo community in increasing awareness of the Kelapa Gading community about the importance of exercise, especially through calisthenics. A less active urban lifestyle can reduce health, so this community offers a flexible and affordable sports alternative. The study used a qualitative descriptive method with observation, interview, and documentation study techniques. The analysis is based on the four-stage communication strategy theory of Cutlip, Center, and Broom, namely fact-finding, strategic planning, implementation, and evaluation. The results of the study show that this community uses social media such as Instagram, TikTok, and Google Maps as the main means of disseminating information and sports campaigns. In addition, face-to-face communication through discussions and direct invitations is also applied to attract community participation. This strategy has proven effective in increasing community awareness and involvement in calisthenics. This study is expected to be a reference for other sports communities in developing communication strategies to increase awareness of the importance of health and exercise.